Clinicopathological and immunohistochemical characteristics of surgically treated primary carcinoma of the nasal vestibule – an evaluation of 30 cases. (June 2015) - Koopmann, M.; Weiss, D.; Savvas, E.; Rudack, C.; Stenner, M.
<x xml:space="preserve">Abstract</x> Objectives/hypothesis Squamous cell carcinoma of the nasal vestibule (SCCNV) is a rare tumour entity. Treatment modality, particularly indication of neck dissection, is still a controversial subject of debate. We sought to evaluate the occurrence of lymph node metastases, the prognosis and the immunohistochemical characteristics of SCCNV. Study Design Retrospective cohort study. Methods This study included 30 consecutive patients with SCCNV treated with primary tumour resection and neck dissection in cases of suspicious lymph nodes between 2003 and 2013. According to therapeutical standard adjuvant radiotherapy or chemotherapy were applied in some cases. Clinicopathological data and immunohistochemical expression of CK5/6, EGFR, Ki‐67, MMP‐2, MMP‐9, p53 and VEGFR were analysed. Results The median follow‐up period was 47.1 months. Five‐year disease‐free (5‐year DFS) and 5‐year overall survival (5‐year OS) were 91.7% and 92.3%. Five‐year OS in low‐grade tumours (G1, G2) was 100.0%, in high‐grade tumours (G3) 75.0% (P = 0.028), respectively. We did not detect any lymph node metastases in the neck dissections. Overexpression of p53 showed a trend for better 5‐year OS (p53‐positive 100% versus p53‐negative 77.8%, n.s.). We found a positive correlation between p53 and EGFR (P = 0.0001). There was no significant relationship between the expression rates of the markers and tumour stage and grading. Conclusions We propose no prophylactic neck dissection in small‐sized SCCNV. Subtile endoscopic follow‐up and periodic ultrasound examination of the cervical lymph nodes after surgical treatment are recommended. Further evaluation of the p53‐ and EGFR‐pathways might pave the way to identify possible molecular targets in an attempt to tailor tumour management.